2021
DOI: 10.21273/hortsci15502-20
|View full text |Cite
|
Sign up to set email alerts
|

How Carbon Source and Seedcoat Influence the In Vitro Culture of Peach (Prunus persica L. Batsch) Immature Seeds

Abstract: The effects of carbon source and concentration and of seedcoat were tested on the in vitro germination of peach seeds derived from crosses performed in the field. Seeds were extracted from the fruit and cultured in Woody Plant Medium (WPM) supplemented with sucrose, glucose, or sorbitol at concentrations of 15, 30, and 45 g·L−1. The percentage of germination as well as the root and hypocotyl lengths were measured after the stratification process and before acclimatization. Seedcoat did not have any influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Our results showed that seed scarification by removing the seed tips significantly increased the speed and frequency of seed germination. In line with our results, Pérez-Jiménez et al [31] reported that seed scarification (i.e., removal of the seed coat) significantly increased the in vitro seed germination of Prunus persica L. Batsch. For the first time, we have demonstrated this method with respect to the micropropagation of cannabis.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that seed scarification by removing the seed tips significantly increased the speed and frequency of seed germination. In line with our results, Pérez-Jiménez et al [31] reported that seed scarification (i.e., removal of the seed coat) significantly increased the in vitro seed germination of Prunus persica L. Batsch. For the first time, we have demonstrated this method with respect to the micropropagation of cannabis.…”
Section: Discussionsupporting
confidence: 92%